2014
DOI: 10.1590/s1679-45082014ao3200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal diabetes on female offspring

Abstract: Objective To evaluate the effect of maternal diabetes on the blood pressure and kidney function of female offspring, as well as if such changes exacerbate during pregnancy.MethodsDiabetes mellitus was induced in female rats with the administration of streptozotocin in a single dose, one week before mating. During pregnancy, blood pressure was measured through plethysmography. On the 20th day of pregnancy, the animals were placed for 24 hours in metabolic cages to obtain urine samples. After the animals were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Moreover, MS-exposed pups also present hypernatremia and hyperaldosteronemia, together with a high level of renal Na + reabsorption, leading to a hypertensive status, detected in these animals one week later. Similar data relative to renal programming changes focused on the effects of maternal nutritional status during intrauterine development have been found (9)(10)(11)(12)14,52). All point to a glomerular hypertrophy with podocyte damage and to inappropriate sodium retention as the main cause of renal injury and hypertension.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Moreover, MS-exposed pups also present hypernatremia and hyperaldosteronemia, together with a high level of renal Na + reabsorption, leading to a hypertensive status, detected in these animals one week later. Similar data relative to renal programming changes focused on the effects of maternal nutritional status during intrauterine development have been found (9)(10)(11)(12)14,52). All point to a glomerular hypertrophy with podocyte damage and to inappropriate sodium retention as the main cause of renal injury and hypertension.…”
Section: Discussionsupporting
confidence: 60%
“…Since MS is related to CVD, it has been demonstrated that it could contribute to the development and progression of chronic kidney disease (CKD) in the human population (7,8). Moreover, important renal programming changes have been described in rats exposed to a high-fructose-diet-induced MS model during gestation and lactation (9,10) and in pups whose mother suffers DM (11)(12)(13). In general terms, the renal programming found is associated to future programmed hypertension (HTA) by genes related to nephrogenesis, renin-angiotensin system (RAS), epigenetic regulators in the kidney and oxidative stress (OE) (9,14).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hyperglycaemic intrauterine conditions lead to the shrinkage of the different renal regions in foe-https://doi.org/10.17221/97/2019-VETMED tuses except for the medullary region (Table 3 and Figure 4). Although there are no contemporary studies present to compare these data, though Martins et al (2014) recorded defective renal functions in threemonth-old pups delivered from diabetic dams. This renal dysfunction may be linked to the defective nephrogenesis due to subnormal uterine environment during the prenatal period in the chronic diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…When children aged 5–18 years were affected, urinary calcium and magnesium excretion was lower in O-T1DM ( 79 ). In animal models, widespread interstitial fibrosis ( 80 ) and severe glomerulosclerosis ( 71 , 81 ) with functional glomeruli loss ( 82 , 83 ) were present at different periods in maternal diabetic offspring, leading to a decreased creatinine clearance ( 87 ), an increased glomerular filtration rate ( 88 ), and microalbuminuria ( 80 ). Urinary calcium and magnesium output was less ( 84 , 85 ), similar to the excretion of basal sodium and urine volume ( 86 ).…”
Section: The Adverse Effects Of Maternal Diabetes On Offspringmentioning
confidence: 99%